Effect of shearing of hair in summer on production of rabbit does - Szendrő, Zsolt; Rashwan, A. A.; Biróné Németh, Edit; Radnai, István; Orova, Zoltán (Acta Agraria Kaposváriensis, 2007)
The aim of the study was to examine the effect of shearing the does’ hair before artificial insemination on their performance in summer. Decreasing the effect of heat stress and increasing of receptivity at the time of AI were expected. Primi- and multiparous Pannon White meat type does were divided into two groups. One half of the animals (n = 80) was sheared (back and both sides of the body) 2 days before the insemination, the other half (non-treated) was the control group (n = 96). Shearing of the does in summer had a positive effect on the daily milk production (227 and 215 g/day, in the sheared and control groups, respectively), and on the litter weight at 35 days of age. Shearing had no effect on litter size but the litter weight was higher by 6, 4 and 9% at 21 (2499 and 2376 g, NS), at 28 (3525 and 3386 g, NS) and at 35 days of age (5816 and 5318 g, P < 0.05). Shearing the rabbit does 2 days before AI as a biostimulation method was judged non-effective. The fertility (67.5 and 67.5%), the litter size, total (9.13 and 8.95) and alive (8.57 and 8.26) was the same in the sheared and control groups. It was concluded that the shearing of rabbit does on hot temperature could be an effective method against the heat stress but it is not recommended using it as a biostimulation method.
Keywords: rabbits does; shearing; biostimulation; milk production